Le Devoir et le groupe des conservateurs-nationalistes après les élections fédérales du 21 septembre 1911 - Moreau, Aurélie (Université d'Angers, 2002)
Keywords: Devoir (Le); Nationalisme; Élections

From Bourassa to Bourassa: Wilderness to Restoration - MacDonald, L. Ian (McGill-Queen's University Press, 2002)
"From Bourassa to Bourassa is a narrative history of the Quebec Liberal Party during its wilderness years after the 1976 election of the Parti Quebecois and its subsequent restoration in 1985." "First published to critical acclaim in 1984, From Bourassa to Bourassa, 2nd edition, updates the story with Bourassa's landslide election victory in 1985 and his subsequent role in the Meech Lake Accord and the Canada-U.S. Free Trade Agreement, the two issues that largely defined the decade of the 1980s for Quebec and for Canada."--BOOK JACKET.
Keywords: Bourassa, Robert; Partis politiques